The Influence of Auditor Reputation, Company Size, Profitability and Auditor Turnover on Audit Delay in Banking Companies Listed On the IDX, 2019 - 2021) - Nainggolan, Benny Rojeston Marnaek; Lawrence, Kellyvani; Fennyenti, Fennyenti; Setio, Klara; Situmorang, Dokman Marulitua (Budapest International Research and Critics University, 2023)
Banking is everything that concerns the Bank, including institutions, business activities as well as methods and processes for carrying out business activities. This research aims to determine and describe the influence of auditor reputation, company size, profitability and auditor turnover on audit delays in banking companies registered on BEI in 2019 - 2021). The method implemented in the research is quantitative through purposive sampling, in the form of 29 banking companies listed on the Indonesia Stock Exchange in 2019-2021. Auditor Reputation, Company Size, Profitability and Auditor Changes have no effect on Audit Delay in banking companies listed on the IDX in 2019 - 2021.